Electrochemical synthesis and supercapacitor performance of manganese and cerium oxide-doped polyaniline composites - Kalyon, Hilal Yildirim; Karasan, Yakup Fatih; Gencten, Metin (IOP Publishing Ltd, 2025)
In this study, polyaniline-based conductive polymers doped with manganese oxide and cerium oxide were electrochemically synthesized for the first time. Unlike previous studies, manganese oxide and cerium oxide doped polyaniline synthesis was carried out in perchloric acid. The resulting composite materials were characterized using spectroscopic and microscopic techniques. The doped polyaniline composites were employed as electrode components in supercapacitors and analyzed using cyclic voltammetry and electrochemical impedance spectroscopy. Changes in capacitive behavior over cycling were examined via galvanostatic charge-discharge measurements. The areal capacitance of the cerium oxide and manganese oxide doped polyaniline electrodes, synthesized under optimal conditions, were measured as 950 mF cm-2 and 660 mF cm-2, respectively, at a charge-discharge current of 10 mA cm-2.
Keywords: manganese; cerium; electrochemical supercapacitor; metal oxides; conductive polymers; HYBRID NANOCOMPOSITES; ELECTRODE MATERIALS; CONDUCTING POLYMER; ENERGY-STORAGE; CARBON; PERCHLORATE; MORPHOLOGY; ANILINE; GRAPHENE/POLYANILINE; NANOSTRUCTURES; Science & Technology - Other Topics; Materials Science; Physics